Beginning OpenOffice Calc From Setting Up Simple Spreadsheets to Business Forecasting - Artymiak, Jacek (Apress : Imprint: Apress, 2011)
OpenOffice Calc is the most powerful and widespread open source spreadsheet application in existence. It is the only real alternative to Excel. Jacek Artymiak is widely regarded as the authority on OpenOffice Calc. He takes you, step by step, from the interface and handling Calc files to working with data sources small and large. Artymiak then extends the reader's skillset to data visualization, writing complex formulas and performing statistical analysis. Beginning OpenOffice Calc allows you to gain confidence in the considered use of statistical formulas, but does not assume familiarity with another spreadsheet application.